Trends and significances of Jordanian media content about the war in Gaza: “Queen Rania’s posts as a model” (October 7, 2023, until January 31, 2024) - Alzubi, Solafah Farouq; Aleessawi, Najm Abed Khalaf Alhatimi (Dirasat: Human and Social Sciences, 2025)
Objectives: The article aims to reveal the contents, trends, and implications of Queen Rania’s media discourse regarding the war in Gaza that occurred on October 7, 2023, covering the period from October 7, 2023, until January 31, 2024. Methods: Content analysis method was employed, classifying media content into categories relevant to the study’s problem. The study sample consisted of Queen Rania’s posts on her Instagram, Facebook, Twitter, YouTube accounts, television interviews, and published articles during the study period. Results: The study showed that there were 37 posts by Queen Rania during the study period, distributed as follows: on Instagram 54.1%, Facebook 24.3%, Twitter -X 16.2%, and YouTube 5.4%. The most common topics were "human rights" and "peace" (27%) each separately. As for the trends, the trend of “conviction” ranked first (29.75%), then the trend of “mobilization and support” and “calling the world for a position” (27%) each separately. In terms of post elements, “text and video” and “text and image” came at a rate of (35.1%) each. Then “video” (18.9%), and finally “text only” (10.8%). Regarding follower interaction, there was “high” interaction (81.1%), followed by “medium” interaction (18.9%). Conclusions: Queen Rania’s media content about the war on Gaza consisted of humanitarian messages representing Jordan’s state policy towards Palestine, clearly expressing support, condemnation of the targeting of the Palestinian people, and calling for a genuine and serious global stance to halt Israeli violations Israeli violations.